Autologous stem cell transplantation in T-cell/histiocyte-rich large B-cell lymphoma: EBMT Lymphoma Working Party study - Renders, Simon; Ngoya, Maud; Finel, Herve; Rubio, Marie-Thérèse; Townsend, William; Schroers, Roland; Novak, Urban; Schaap, Nicolaas; Aljurf, Mahmoud; Helbig, Grzegorz; Collin, Matthew; Kobbe, Guido; et al. (Blood advances, 2024)
Although broadly used, consolidative autologous hematopoietic stem cell transplantation (auto-HCT) for relapsed/refractory (R/R) T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL) has never been specifically investigated. Here, we have analyzed outcomes of auto-HCT for THRLBCL compared with diffuse large cell B-cell lymphoma not otherwise specified (DLBCL). Eligible for this retrospective registry study were adult patients with R/R THRLBCL and DLBCL, respectively, who underwent a first auto-HCT in a salvage-sensitive disease status as assessed by positron emission tomography-computed tomography between 2016 and 2021 and were registered with the European Society for Blood and Marrow Transplantation database. The primary end point was progression-free survival (PFS) 2 years after transplantation. A total of 201 patients with THRLBCL and 5543 with DLBCL were included. There were no significant differences in terms of disease status at HCT, pretreatment lines, and interval from diagnosis to transplant between the cohorts, but patients with THRLBCL were significantly younger, contained a higher proportion of men, and had a better performance status. Compared with DLBCL, THRLBCL was associated with significantly better 2-year PFS (78% vs 59%; P < .001) and overall survival (OS, 81% vs 74%; P = .02) because of a significantly lower 2-year relapse incidence (16% vs 35%; P < .001). On multivariate analysis, favorable relapse risk (hazard ratio [HR], 0.46; 95% confidence interval [CI], 0.31-0.7) and PFS (HR, 0.58; 95% CI, 0.41-0.82) of patients with THRLBCL remained significant, whereas OS benefits (HR, 0.78; 95% CI, 0.54-1.12) did not. These results were validated in a propensity score-matched analysis. These data prove auto-HCT as an effective treatment option for salvage-sensitive R/R THRLBCL.
Online veröffentlicht: 25. Oktober 2024
Gesehen am 10.09.2025